2017
DOI: 10.1038/s41598-017-13996-8
|View full text |Cite
|
Sign up to set email alerts
|

A New Generation of Arachidonic Acid Analogues as Potential Neurological Agent Targeting Cytosolic Phospholipase A2

Abstract: Cytosolic phospholipase A2 (cPLA2) is an enzyme that releases arachidonic acid (AA) for the synthesis of eicosanoids and lysophospholipids which play critical roles in the initiation and modulation of oxidative stress and neuroinflammation. In the central nervous system, cPLA2 activation is implicated in the pathogenesis of various neurodegenerative diseases that involves neuroinflammation, thus making it an important pharmacological target. In this paper, a new class of arachidonic acid (AA) analogues was syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Recently, a new generation of AA analogues was developed as potential neurological agents targeting GIVA cPLA 2 [43]. Among these compounds, inhibitor 10 ( Fig.…”
Section: Inhibitors Of Cytosolic Phospholipase Amentioning
confidence: 99%
“…Recently, a new generation of AA analogues was developed as potential neurological agents targeting GIVA cPLA 2 [43]. Among these compounds, inhibitor 10 ( Fig.…”
Section: Inhibitors Of Cytosolic Phospholipase Amentioning
confidence: 99%
“…Moreover, a pro-inflammatory role of cadaverine was observed in a recent in vivo study ( Fan et al, 2012 ). Similarly, arachidonic acid is a polyunsaturated fatty acid which plays an important role in mediation of a variety of inflammation responses and initiation of oxidative stress via serving as the precursor for the synthesis of eicosanoids and prostanoids ( Ng et al, 2017 ). In this study, 1-week ISO intervention was found to downregulate plasma levels of both cadaverine and arachidonic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we also obtained evidence of increased phospholipase A 2 activity [ 25 ], readily detected in terms of arachidonic acid release after stimulation with 10 μ M A23187 or 200 μ M peroxynitrite ( Figure 1(d) ). AACOCF 3 , a well-established inhibitor of cytosolic phospholipase A 2 [ 36 ], suppressed arachidonic acid release detected under both circumstances.…”
Section: Resultsmentioning
confidence: 99%